A randomized, prospective, masked clinical trial comparing an opioid-free vs. opioid-sparing anesthetic technique in adult cats undergoing ovariohysterectomy - Rufiange, Maxime; Ruel, Helene L. M.; Monteiro, Beatriz P.; Watanabe, Ryota; Cruz Benedetti, Inga-Catalina; Benito, Javier; Steagall, Paulo V. M. (Frontiers in Veterinary Science, 2022)
This study aimed to compare the analgesic effects of an injectable protocol using multimodal analgesia with or without opioids in cats undergoing ovariohysterectomy (OVH). Thirty-two healthy cats were enrolled in a prospective, blinded, randomized trial after the caregiver’s written consent. Cats received a combination of ketamine (4 mg/kg), midazolam (0.25 mg/kg) and dexmedetomidine (40 μg/kg), and either buprenorphine (20 μg/kg) or saline (same volume as buprenorphine) intramuscularly [opioid-sparing (OSA) and opioid-free anesthesia (OFA) groups, respectively]. Intraperitoneal bupivacaine 0.25% (2 mg/kg) and meloxicam (0.2 mg/kg subcutaneously) were administered before OVH. Atipamezole (400 μg/kg intramuscularly) was administered at the end of surgery. Pain and sedation were evaluated using the Feline Grimace Scale (FGS) and a dynamic interactive visual analog scale, respectively. Intravenous buprenorphine was administered as rescue analgesia if FGS scores ≥ 0.39/1. Statistical analysis included repeated measures linear mixed models, Fisher’s exact test and Bonferroni adjustments when appropriate (p < 0.05). Twenty-seven cats were included. The prevalence of rescue analgesia was lower in OSA (n = 0/13) than in OFA (n = 5/14) (p = 0.04). The FGS scores (least square means and 95% CI) were higher in OFA at 1h [2.0 (1.3-2.7)] and 2h [2.2 (1.5-2.9)] than baseline [0.7 (0.0-1.4)], but not in OSA. Sedation scores were not significantly different between groups. Opioid-free injectable anesthesia was appropriate for some cats using a multimodal approach. However, a single dose of intramuscular buprenorphine eliminated the need for rescue analgesia and assured adequate pain management after OVH in cats.